Provision of environmental goods on potentially abandoned land : the White Carpathian protected landscape area - Tomás Ratinger; Veronika Krumalová (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2001)
At the beginning of the transition, the economic decline of agriculture partially relaxed the pressure on the wildlife. However, the policy continued to concentrate on regulating the intensity of production rather then creating incentives to produce environmental qualities. The structural adjustment process in agriculture caused the low return (poor) land to be released from production, especially, in protection zones with severe environmental restrictions. Land abandonment resulted in a rapid degradation of wildlife and landscape in places where these natural values were legally protected. The article examines the organisation of the provision of landscape and wildlife in the White Carpathians protected landscape area after 1997, when the new agricultural legislation and policy recognised compensations for restrictions and has gradually introduced incentives to cultivate potentially abandoned land. It was found that there was more than one governance structure, and that these were not necessary supporting each other. Our investigation concluded that solving the conservation problem is not separable from the rural development problem of the region, and therefore, that there is a need for participation of local community in terms of contributing producers but mainly consumers of high natural values.
Keywords: 330; Naturschutz; Agrarpolitik; Landschaftspflege; Karpaten